Combining dielectrophoresis and concentration polarization-based preconcentration to enhance bead-based immunoassay sensitivity. Issue 19 (30th April 2019) - Park, Sinwook; Yossifon, Gilad
Abstract : Ionic concentration-polarization (CP)-based simultaneous preconcentration of functionalized nanoparticles and target biomolecules followed by dynamic trapping of the beads using dielectrophoresis (DEP) for binding signal assessment. Abstract : Ionic concentration-polarization (CP)-based biomolecule preconcentration is an established method for enhancing the detection sensitivity of a target biomolecule immunoassay. However, its main drawback lies in its inability to directly control the spatial overlap between the preconcentrated plug of biomolecules and the surface immobilized antibodies. To overcome this, we simultaneously preconcentrated freely suspended, surface functionalized nanoparticles and target molecules along the edge of a depletion layer, thus, increasing the binding kinetics and avoiding the need to tune their relative locations to ensure their spatial overlap. After the desired incubation time, the nanoparticles were dielectrophoretically trapped for postprocessing analysis of the binding signal. This novel combination of CP-based preconcentration and dielectrophoresis (DEP) was demonstrated through binding of avidin and biotin-conjugated particles as a model bead-based immunoassay, wherein increased detection sensitivity was demonstrated compared to an immunoassay without CP-based preconcentration. The DEP trapping of the beads following binding is important not only for an enhanced detection signal due to the preconcentration of the beads at the electrode edges but also for controlling their location for future applications integrating localized sensors. In addition, DEP may be important also as a preprocessing step for controlling the number of beads participating in the immunoassay.